Overestimation of alcohol consumption norms as a driver of alcohol consumption: a whole-population network study of men across eight villages in rural, southwestern Uganda - Perkins, Jessica M.; Kakuhikire, Bernard; Baguma, Charles; Jurinsky, Jordan; Rasmussen, Justin D.; Satinsky, Emily N.; Namara, Elizabeth; Ahereza, Phionah; Kyokunda, Viola; Perkins, H. Wesley; Hahn, Judith A.; Bangsberg, David R.; et al. (Addiction, 2022)
Background and aims Little is known about how perceived norms about alcohol consumption may influence high alcohol consumption rates in Uganda. This study estimated the accuracy of perceived norms about men’s alcohol consumption and estimated the association between perceived norms and personal alcohol consumption. Design Cross-sectional, whole-population, sociocentric social network study. Setting Eight rural villages in Rwampara District, southwestern Uganda in 2016–18. Participants A total of 719men aged 18 years and older (representing 91% of permanent resident men). Measurements Self-reported frequent (≥ 4 days per week) and heavy alcohol consumption (six or more drinks on one occasion, more than three occasions of intoxication, or spending an excessive amount on alcohol). Participants also reported whether they thought most other men in their village engaged in frequent and heavy alcohol consumption (perceived norms). Using the network study design, we calculated alcohol consumption behavior within villages and social networks. Perceived norms were compared with aggregated self-reports. Multivariable Poisson regression models were used to estimate the association between perceived norms and individual behavior. Findings Throughout villages, frequent and heavy alcohol consumption ranged from 7 to 37%. However, 527 (74%) participants perceived, contrary to fact, that most other men in their villages frequently consumed alcohol, and 576 (81%) perceived that most others heavily consumed alcohol. Overestimation of alcohol consumption by others was pervasive among socio-demographic subgroups and was present irrespective of the actual consumption behavior at the village level and within social networks. Men who misperceived these alcohol consumption behaviors as being common were more likely to engage in frequent [adjusted relative risk (aRR) = 3.98; 95% confidence interval (CI) = 1.69–9.34) and heavy (aRR = 4.75; 95% CI = 2.33–9.69) alcohol consumption themselves. Conclusions Most men in eight rural Ugandan villages incorrectly thought that frequent and heavy alcohol consumption were common among men in their villages. These misperceived norms had a strong positive association with individual drinking behavior.
Keywords: Alcohol consumption; Alcohol use; Binge drinking; Descriptive norms; Misperception; Perceived norms; Social networks; Social norms; Sub-Saharan Africa; Uganda